LIFE AND WORK OF THE POET BAZARBAI IMANOV (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
Poet Bazarbai Imanov was born and raised in the Shomanai district of the Republic of Karakalpakstan. In that soil, his poetic talent was awakened and he published several collections of poems. Today, Ata has moved to Aktobe, Republic of Kazakhstan. His poems are philosophically liked by his readers. The themes of his poems appeal to love for the native land, devotion, love, morality and honesty.